SUBALGEBRAS AND FINITISTIC DIMENSIONS OF ARTIN ALGEBRAS - 张爱平 张顺华 (Acta mathematica scientia, 2011)
Let A be an Artin algebra.We investigate subalgebras of A with certain conditions and obtain some classes of algebras whose finitistic dimensions are finite.